Vat photopolymerization of liquid, biodegradable PLGA-based oligomers as tissue scaffolds. (5th May 2020) - Wilts, Emily M.; Gula, Aleena; Davis, Corey; Chartrain, Nicholas; Williams, Christopher B.; Long, Timothy E.
Graphical abstract: Highlights: Ring-opening polymerization with subsequent end-group functionalization yielded PLGA-diacrylates. Six different ratios of lactide and glycolide copolymers produced varying degradation rates and zero-shear viscosities. Photocalorimetry and photorheology revealed decreasing acrylate conversion with increasing zero-shear viscosity. Preliminary cytotoxicity studies revealed a maintenance of 70% viability over 72 h for selected samples. Abstract: Additive manufacturing (AM) of tissue scaffolds provides medical professionals and patients with personalized treatment options, which align with patients' specific physiology and provide a more efficient and precise manufacturing process. Vat photopolymerization (VP) AM affords biocompatible, degradable, and high-resolution scaffolds capable of achieving specific pore sizes necessary for tissue regeneration. Earlier biodegradable, photoactive polymers for the VP platform usually require dissolution in a solvent or water, which often results in anisotropic shrinkage upon drying and inconsistencies in the final part geometry. This work describes a photoactive oligomeric precursor that eliminates the requirement for water or solvent during VP. Poly(lactide- co -glycolide) (PLGA) diacrylates with low number-average molecular weights (< 1400 g mol −1 ) provided liquid, viscous precursors. Upon crosslinking, the networks exhibited mechanical strength and low cytotoxicity, which are prerequisites for soft tissue scaffolds. Systematically varying the ratios of lactide to glycolide provided a range of degradation rates from 4 to 12 wks. Tailored degradation rates will enable use in different anatomical environments. Cytotoxicity and cell attachment studies revealed crosslinked films that promoted cell growth and proliferation. This manuscript describes an expanded polymer toolbox for AM of tissue scaffolds with precise resolution in the absence of solvents.